AB0658 Factors influencing elapsed time to a definitive diagnosis of systemic sclerosis and their relationship with the number of attending physicians and their medical specialization. (15th June 2017) - Erez, Y; Tugsal, H Yarkan; Kenar, G; Zengin, B; Solmaz, D; Ozmen, M; Can, G; Akkoc, N; Onen, F; Birlik, M
Abstract : Background: The diagnosis of Systemic Sclerosis (SSc) can be difficult due to its rarity and heterogeneity. In addition, not all physicians are expert in the identification of patients with early SSc features. Objectives: The aim of this study was to investigate factors influencing the time elapsed since a proper diagnosis of SSc and their relationship with the number of attending physicians and their specialization, among Turkish patients. In Turkish healthcare system, each patient may directly go to the hospitals and choose appropriate care facility and physician. Methods: The study covers 240 SSc patients who were diagnosed according to 1980 ACR criteria in the rheumatology database at the University of Dokuz Eylul, Izmir. Data included demographics, SSc duration, SSc subtype, physical examinations (mRodnan Score-mRS), and a face-to-face structured interview. Cases were excluded if they couldn't recall date of initial symptoms and all the prior attending physicians including their specialization until a definitive diagnosis of SSc. As clinical characteristics are different than pure SSc patients, overlap syndromes were excluded. Mann-Whitney U test was used to assess the difference between dependent and independent variables. The association between mRS and dependent variables was evaluated by Spearman correlation test. Results: Remaining 135 patients (F:88.8%), mean age±SD (52.14±11.58 years) identified. 55 (41%) patients had diffuse and 80 (59%) patients had limited disease. 119 (88%) patients SSc diagnosed by a rheumatologist however, 48 patients (35%) were first seen by an internist. Median time to diagnosis was 36 months (1–588) from the onset of Raynaud Phenomenon (RF) and 11 months (0–397) from the onset of the first non-RF symptom for our cases. Relation between some parameters and time to diagnosis were shown in Table.1 . Mean number of attending physicians until SSc diagnosis was calculated as 3, 54 (SD±1, 66). None of the demographic and clinical parameteres (SSc subtype, mRS, symptom duration) were related with the number of attending physician. There was no correlation detected between mRS and time to diagnosis and number of attending physicians. Nevertheless it was established that median number of physicians was less for patients who were referred to a proper clinician by their familier healthcare practitioners (p: 0, 019). Conclusions: Time to diagnosis from onset of RF is significantly shorter in diffuse SSc. Although mRS is typically higher in diffuse SSc, no correlation has been found between mRS and time to diagnosis. Therefore, duration of diagnosis may be influenced by internal organ involvement and other complications rather than skin changes due to lack of awareness of physicians about SSc related early skin changes. Referral to a proper physician by a familier healthcare practitioner decreased the number of physicians attending till the diagnosis, although it did not affect the time to diagnosis. Disclosure of Interest: None declared